High‐milking sheep have a lower ovulation rate and tend to yield fewer embryos in response to superovulation and intrauterine artificial insemination. (29th April 2017) - Meraï, A; Dattena, M; Casu, S; Rekik, M; Lassoued, N
Contents: Antagonistic relationship between milk yield and reproduction is reported in several livestock species. This study aimed to investigate whether genetic merit for milk production in dairy sheep affects responses to superovulation, embryo yield and quality. A total of 21 cross‐bred Sarda x Lacaune ewes homogeneous for age, parity and stage of lactation were included. The ewes were stratified as high‐producing or low‐producing based on their genetic merit for milk production estimated by a pentatrait repeatability animal model. Oestrus was synchronized using an intravaginal progesterone pessary inserted on Day 0 and removed on Day 14. Superovulatory treatment consisted of 350 I.U. of porcine FSH administered in eight decreasing intramuscular doses every 12 hr with a total dose of 10 ml of solution starting 12 days after insertion of sponges. Laparoscopic artificial insemination (AI) was performed 48 hr after pessary removal. Surgical embryo recovery was performed at Day 8 after pessary removal. Correlation between breeding value for milk production and the number of corpora lutea (CL) was significantly different from zero (−0.49). High‐producing ewes had a lower number of CL than low‐producing counterparts (7.6 ± 2.50 vs 12.1 ± 5.16 respectively; p < .02). Furthermore, there was a tendency for high‐producing ewes to yield fewer embryos than low‐producing females (5.3 ± 3.46 vs 9.18 ± 5.11; p = .09). No differences were observed between ewes in both genetic groups with regard to the number of embryos of grades 1, 2 and 3. To our knowledge, this is the first report highlighting an antagonism between genetic merit for milk production and the ability to produce embryos in sheep. These results deserve to be considered in sheep breeding programmes.